Pendampingan Sertifikasi Halal dan NIB bagi UMKM di Kelurahan Bendung, Kec. Kasemen, Kota Serang: Penelitian - Desty Endrawati Subroto; Mardia Ulfah; Zia’ul Fatwa Andini Yusuf; Gita Anggraini; Aris Widodo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Halal certification and Business Identification Number (NIB) assistance for Micro, Small, and Medium Enterprises (MSMEs) in Bendung Village, Kec. Kasemen, Serang City, is a strategic effort to improve the legality and competitiveness of local products. Halal certification is crucial for ensuring product halalness, increasing consumer trust, and supporting sharia-based economic growth, especially in Muslim-majority communities. This activity is a collaboration between undergraduate and postgraduate students in Group 05 KKM of Bina Bangsa University in collaboration with Bendung Village and the Halal Center Assistance Institution of Sultan Ageng Tirtayasa University. The assistance method includes socialization, assistance in filling out documents, and technical training on registration through the OSS. Participants were 15 Micro, Small, and Medium Enterprises. The results of the activity indicate an increase in MSMEs' understanding of the importance of halal certification and NIB, thus encouraging them to be more active and orderly in complying with applicable regulations. This program is expected to create legal, competitive MSMEs with a product reputation that is trusted by consumers.